Use of a novel chagas urine nanoparticle test (chunap) for diagnosis of congenital chagas disease. - Yagahira E Castro-Sesquen; Robert H Gilman; Gerson Galdos-Cardenas; Lisbeth Ferrufino; Gerardo Sánchez; Edward Valencia Ayala; Lance Liotta; Caryn Bern; Alessandra Luchini; Working Group on Chagas Disease in Bolivia and Peru (PLoS Neglected Tropical Diseases)
Background Detection of congenital T. cruzi transmission is considered one of the pillars of control programs of Chagas disease. Congenital transmission accounts for 25% of new infections with an estimated 15,000 infected infants per year. Current programs to detect congenital Chagas disease in Latin America utilize microscopy early in life and serology after 6 months. These programs suffer from low sensitivity by microscopy and high loss to follow-up later in infancy. We developed a Chagas urine nanoparticle test (Chunap) to concentrate, preserve and detect T. cruzi antigens in urine for early, non-invasive diagnosis of congenital Chagas disease. Methodology/principal findings This is a proof-of-concept study of Chunap for the early diagnosis of congenital Chagas disease. Poly N-isopropylacrylamide nano-particles functionalized with trypan blue were synthesized by precipitation polymerization and characterized with photon correlation spectroscopy. We evaluated the ability of the nanoparticles to capture, concentrate and preserve T. cruzi antigens. Urine samples from congenitally infected and uninfected infants were then concentrated using these nanoparticles. The antigens were eluted and detected by Western Blot using a monoclonal antibody against T. cruzi lipophosphoglycan. The nanoparticles concentrate T. cruzi antigens by 100 fold (western blot detection limit decreased from 50 ng/ml to 0.5 ng/ml). The sensitivity of Chunap in a single specimen at one month of age was 91.3% (21/23, 95% CI: 71.92%-98.68%), comparable to PCR in two specimens at 0 and 1 month (91.3%) and significantly higher than microscopy in two specimens (34.8%, 95% CI: 16.42%-57.26%). Chunap specificity was 96.5% (71/74 endemic, 12/12 non-endemic specimens). Particle-sequestered T. cruzi antigens were protected from trypsin digestion. Conclusion/significance Chunap has the potential to be developed into a simple and sensitive test for the early diagnosis of congenital Chagas disease.